The use of growth velocity z-scores to early detect growth faltering in Indonesian infants - Dinari, Rizka; Oktaria, Vicka; Danchin, Margie (BKM Public Health and Community Medicine, 2021)
Objective: This study aimed to describe infant growth patterns using attained growth z-scores and growth velocity z-scores in the first year of life in Indonesia. Method: A cohort study of 359 newborns was conducted in 2015-2017 in Yogyakarta, Indonesia. Weight and length were routinely measured throughout the first year of life to calculate the attained growth z-scores (weight-for-age/WAZ, length-for-age/LAZ, and weight-for-length z-scores/WLZ) and growth velocity z-scores (weight velocity/WVZ and length velocity z-scores/LVZ). Undernutrition was categorized into underweight (WAZ<-2), stunting (LAZ<-2), and wasting (WLZ<-2). Growth faltering was categorized into weight faltering (WVZ<5th centile) and length faltering (LVZ<5th centile) using WHO child growth standards. Results: The proportion of undernutrition and growth faltering varied throughout infancy. The highest proportion of undernutrition was the proportion of stunting at 12 months (15.3%) which was two times higher than at birth (7.3%). The highest proportion of weight and length faltering was in 4-6 months with 28.6% and 39.4%, respectively. Median WAZ was relatively stable at around -0.30 SD in the first six months before it slightly decreased to -0.64 SD at 12 months of age. Median LAZ increased from -0.62 SD at birth to -0.23 SD at four months before declining to -0.83 SD at 12 months. In comparison to attained growth z-scores, growth velocity z-scores depicted an opposing pattern. Median WVZ decreased from 0.33 SD at 0-2 months to -0.80 SD at 4-6 months, while median LAZ dropped from 1.33 SD at 0-2 months to -1.20 SD at 6-9 months. Conclusion: The proportions of undernutrition and growth faltering were relatively high in the first year of life. Growth velocity z-scores showed an earlier downward pattern than attained growth z-scores. Therefore, routine monitoring, particularly in growth velocity z-scores, might allow earlier detection and treatment of child growth faltering.